Review of ship safety domains: Models and applications. (15th November 2017) - Szlapczynski, Rafal; Szlapczynska, Joanna
Abstract: Ship safety domain is a term which is widely used in research on collision avoidance and traffic engineering among others. Classic ship domains have been compared in multiple reports. However, up till now there has been no work summing up contemporary research in this field. The paper offers a systematic and critical review of the newer ship domain models and related research. It discusses multiple differences in approach to ship domain concept: from definitions and safety criteria, through research methodologies and factors taken into account, to sometimes largely different results obtained by various authors. The paper also points out some interpretation ambiguities related to ship domain and sums up present trends of its development and applications. Highlights: Offers a critical review of contemporary ship domain models. Features an analysis and comparison of ship domain-related safety criteria. Includes a classification of ship domains in terms of their purposes and research methods. Provides a brief summaries of all major ship domain models. Concludes with a prediction of ship domains future research and applications.